A mass production paper-making method to prepare superior flexible electrodes and asymmetric supercapacitors with high volumetric capacitance. (20th January 2021) - Bi, Jingxuan; Wu, Haiwei; Wang, Li; Pang, Xiaofei; Li, Yiyi; Meng, Qingjun; Wang, Lei
Highlights: Report a mass production paper-making method for flexible electrodes. The HWF supported paper electrodes show high volumetric capacitance of 246.4 f cm −3 and good flexibility. The HWF supported ASCs achieve a high energy density of 10.1 mWh cm −3 with power density of 93.9 mW cm −3 . Abstract: In this study, paper supported flexible electrodes for supercapacitors are prepared by paper-making process with the hardwood fiber (HWF), multi-walled carbon nanotube (MWCNT) and NiCo2 S4 powder. Compared with previous reported cellulose nanofiber (CNF), nickel foam and carbon cloth supported electrodes, the HWF supported paper electrodes demonstrate its advantages of low-cost, mass production, low-thickness and superior flexibility. It can achieve a high specific capacitance of 1725 F g −1 at 1 A g −1, a remarkable rate retention of 79.3 % from 1 A g −1 to 10 A g −1, an ultrahigh volumetric specific capacitance of 246.4 F cm −3 at 1 mA cm −2 and an excellent cycling stability at 20 A g −1 after 5000 cycles. The as-fabricated HWF supported flexible asymmetric supercapacitors (ASCs) have achieved excellent volumetric specific capacitance of 10.25 F cm −3 and energy density of 10.1 mWh cm −3 with power density of 93.9 mW cm −3 . All results suggest that the paper-making method and the HWF supported paper electrodes provide great opportunity for developing high-performance flexible energy-storage electrodes with the feasibility of mass production. Graphical abstract: Image, graphical abstract